Impacts of Sea Bottom Temperature on CPUE of European Lobster Homarus gammarus (Linnaeus, 1758; Decapoda, Nephropidae) in the Eastern Adriatic Sea - Matić-Skoko, Sanja; Pavičić, Mišo; Šepić, Jadranka; Janeković, Ivica; Vrdoljak, Dario; Vilibić, Ivica; Stagličić, Nika; Šegvić-Bubić, Tanja; Vujević, Ante (Frontiers in Marine Science, 2022)
The study describes recent decadal changes (2008–2017) in the landing biomass, fishing effort and CPUE (kg/day) data of European lobster Homarus gammarus in the eastern Adriatic Sea region, and relates these changes to increases of sea bottom temperatures detected at long-term in situ stations and modelled by an ocean numerical model (ROMS, Regional Ocean Modelling System). Modelling results were further used to quantify spatial and temporal differences of bottom temperature changes over different fishing zones. Trends of sea bottom temperature were positive and statistically significant between stations. Temporal trends of landing, effort and CPUE were also positive and significant for the northern Adriatic. Correlation analysis was used to test the relationship between winter and spring sea bottom temperatures and CPUE data of H. gammarus, separately for the northern and central Adriatic Sea, resulting in statistically significant correlations for both areas. Whether the increased CPUE in the northern Adriatic is due to increased abundance or catchability is discussed. The observed temperature changes likely reflect climate system changes recognised at the regional level and as such, lobster management measures will need to be revised and updated in the future.